Cost-effectiveness analysis of first-line cadonilimab plus chemotherapy in HER2-negative advanced gastric or gastroesophageal junction adenocarcinoma - Zhou, Zhifeng; Yang, Yanqing; Chen, Shaofang; You, Maojin (Frontiers in Immunology, 2025)
BackgroundThe COMPASSION-15 trial demonstrated that cadonilimab plus chemotherapy (CAD-CHM) confers clinical benefits over placebo plus chemotherapy (PLA-CHM) as a first-line treatment for human epidermal growth factor receptor 2 (HER2)-negative advanced gastric or gastroesophageal junction (G/GEJ) adenocarcinoma. However, the introduction of cadonilimab substantially elevates treatment costs, and its cost-effectiveness relative to PLA-CHM remains undetermined. This study evaluates the cost-effectiveness of CAD-CHM compared with PLA-CHM from the perspective of the Chinese healthcare system.MethodsA Markov model with three health states was developed to assess the cost-effectiveness of CAD-CHM in HER2-negative advanced G/GEJ adenocarcinoma. Clinical efficacy data were sourced from the COMPASSION-15 trial, while drug costs were calculated based on national tender prices, and additional costs and utility values were extracted from published literature. The analysis encompassed the overall population, as well as subgroups stratified by programmed death ligand 1 (PD-L1) combined positive score (CPS) ≥ 5 and CPS < 5. Outcomes included total costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratios (ICERs). Sensitivity analyses were conducted to evaluate model robustness.ResultsThe ICER of CAD-CHM was $67,378.09 per QALY in the overall population, $48,433.34 per QALY in the PD-L1 CPS ≥ 5 subgroup, and $78,463.86 per QALY in the PD-L1 CPS < 5 subgroup. Key determinants influencing model outcomes included patient weight, cadonilimab cost, and the utility value of progression-free survival. Across all groups, CAD-CHM resulted in an ICER exceeding the willingness-to-pay threshold of $41,511 per QALY, with a 0% probability of cost-effectiveness compared with PLA-CHM.ConclusionFrom the perspective of the Chinese healthcare system, CAD-CHM is not cost-effective as a first-line treatment for HER2-negative advanced G/GEJ adenocarcinoma, either in the overall population or in subgroups stratified by PD-L1 CPS status, compared with chemotherapy alone.